2019
DOI: 10.1002/jsfa.9574
|View full text |Cite
|
Sign up to set email alerts
|

The effect of using different types and rates of onion‐water extract in meatball production on the formation of heterocyclic aromatic amines

Abstract: BACKGROUND The effect of using different types (yellow, white and purple) and rates (0.25%, 0.50% and 0.75%) of onion‐water extract in meatball production on the various quality criteria of meatballs and the formation of heterocyclic aromatic amines (HCAs) was investigated. RESULTS It was determined that cooking process caused a reduction in the water content of meatballs as well as an increase in pH values. MeIQx, 7,8‐DiMeIQx, 4,8‐DiMeIQx, PhIP, AαC and MeAαC could not be detected in any of the analyzed meatb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 82 publications
2
35
0
Order By: Relevance
“…The increase in pH value of meatballs with adding the black cumin could be attributed to the high pH value of the black cumin used in the present study (6,22). Cooking, as expected, caused an increase in pH values of the samples and this finding is in accordance with that reported by others [18,37,40]. In addition, in the present study, it was also determined that the pH values of the samples increased as the cooking temperature increased.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The increase in pH value of meatballs with adding the black cumin could be attributed to the high pH value of the black cumin used in the present study (6,22). Cooking, as expected, caused an increase in pH values of the samples and this finding is in accordance with that reported by others [18,37,40]. In addition, in the present study, it was also determined that the pH values of the samples increased as the cooking temperature increased.…”
Section: Resultssupporting
confidence: 93%
“…In addition, as the usage rate of black cumin increased, MeIQx content of the samples decreased. Although MeIQx was not detected in various meat and meat products [18,35,5963], MeIQx was determined as 0,64 ng/g in fried beef by Wakabayashi et al [64], as 1 ng/g in beef fried at 250°C for 12 min by Felton et al [56], as 2,11 ng/g in broiled beef by Wakabayashi et al [64], up to 8,3 ng/g in beef fried at 190°C for up to 13 min by Gross [65] and as 16,4 ng/g in beef fried at 277°C for 12 min by Thiébaud et al [66]. The maximum MeIQx content was recorded in cooked beef at a concentration level of 80 ng/g [3].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In beef fried at 200 °C for 8 min per side, 2% of onion inhibited the formation of some groups of HAs between 74 and 100%, and the total amount of HAs presented a greater inhibition with 4% of onion; however, from 8%, there was an increase, possibly due to the amount of sugar in onion that could participate of the Maillard reaction and promote the formation of HAs (Dong, Lee, & Shin, 2011). Nuray and Oz (2019) also observed an increase in total HAs as they used onion‐water extract at 0.25, 0.50, and 0.75%, in meatballs fried for 8 min at 200 °C due to MEIQ production; the authors attribute this effect to the amino acid alanine, found in onion, that could be the precursor of this type of amine.…”
Section: Resultsmentioning
confidence: 94%
“…Surprisingly, PUFA contents in garlic-and onion-pretreated samples were signicantly lower than that in control patties. This might be due to the prooxidative effect of some of the constituents in garlic and onion under the experimental conditions, 54,55 which caused oxidative degradation of PUFAs in the patties. The signicantly higher contents of PUFAs in Mongolian leek, Chinese chive and Welsh onion pretreated samples were likely due to their much higher ($10-fold) contents of a-linolenic acid (C18:3n3), 56 an intrinsic property of these three Allium spp.…”
Section: Effect Of Allium Powders On Fatty Acid Proles Of Roasted Comentioning
confidence: 99%